IMPROVING STUDENTS’ LEARNING OUTCOMES USING THE TEAMS GAMES TOURNAMENT LEARNING MODEL IN 5TH GRADE OF SDN 94 PALEMBANG - Maulidya, Elvira; Indaryanti, Indaryanti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
The results of the teaching practice of 5th-grade participants at SDN 94 Palembang still needed improvement due to the teacher’s lecture and question-and-answer learning method. This research aims to improve the participants’ learning outcomes using the TGT training approach. The research adopts a class action research method in two cycles, planning, implementation, observation, and reflection. The success measurement of this research is a minimum of 75% of the students fulfilling the minimum completeness criteria of 75. The research results demonstrate that using the TGT approach can enhance the participants’ learning outcomes. It is apparent from the improvement in the participants’ learning outcomes throughout the research process. In the pre-cycle, only 38% of participants achieved completion with an average score of 63.75. In Cycle I, the number increased to 63% and an average score of 73.75. In Cycle II, the number further increased to 88% and an average score of 93.75.